Lazarillo del Tormes, Islamic Influences and Spanish Perspectives - Mishra, Sabyasachi; Saqib, Mohd; Shandilya, Shantanu (Dirasat: Human and Social Sciences, 2025)
Objectives: Lazarillo de Tormes is a well-known Spanish book, got published in three places in 1554. Narrated in First person, it talks about the hardships of a common person Lazaro, who wants to improve his life. Similarly, it is an era of changes in Spain. The article deals with analysis of protagonist in changing times. Muslims in general, were considered citizens of second generation and common cultural history, which was of shared cultural past not of shared cultural past. Methods: Through the literature review of the Book, the theme has been analyazed and it has tried to demonstrate the book deals with theme of honour, Islamic influences prejudice in the contemporary Spain. Results:. Different authors of Spanish Golden Age opine that contemporary Spain dealt harshly with the Arabic influence in day-to-day life and the sane has been reflected in Lazarillo de Tormes, it deals with perspectives of how both the civilizations came into the contact and Spain has Islam influences in Christian Spain, where people were discriminated on their religious identities. The article deals with the theme of picaresque literature also. Conclusions: It discusses the fear of rejection or public disapproval often leads to distressing concerns. Honor and shame are reciprocal moral values that signify the assimilation of individual into a particular collective. Impact of public opinion and its unwritten rules in early modern Spain is a recurring theme in picaresque novels, and it is particularly evident in Lazarillo de Torres.